Hall deflection of spin-current driven skyrmion and its modulation - Yu Wang; Jingguo Hu (APL Materials)
Skyrmion has been widely studied as a potential novel information carrier due to its particle-like structure and high sensitivity to the external field. However, the application of skyrmion in novel information memory is limited by the Hall deflection originating from its topological structure. Therefore, by analyzing the relationship between the skyrmion Hall deflection and the driving current as well as the properties of ferromagnetic nanoribbons, we obtain an effective method to regulate the Hall deflection and realize smooth movement of skyrmion, so as to ensure the stable reading of information. The regulation controls the magnetization orientation of the ferromagnetic input layer so that the spin current injected vertically into the upper layer can obtain an appropriate lateral spin polarization to suppress the transverse deflection caused by the skyrmion Hall effect, hence ensuring that the spin current drives the skyrmion along the magnetic track steadily. In addition, the modulation mechanism and influencing factors are analyzed in detail.